Adventitious match probability for autosomal profiles when primer binding site mutation is possible. (September 2016) - Pope, Susan; Evett, Ian; Puch-Solis, Roberto
Highlights: Investigates the potential for an adventitious match as a result of a PBSM when a crime profile and person profile from two individuals are the same Demonstrated that the effect of PBSMs is to slightly decrease the adventitious match probability from what it would had the same DNA system been used. This was done by both theory and using simulations. Concludes the probability of an adventitious match between profiles from two individuals being caused by a PBSM in one individual is very small. Abstract: This paper considers the situation where two DNA systems with differing primers have been used to produce DNA profiles for loading and searching of a DNA Database. With any profiling system there exists the possibility of a "primer binding site mutation" (PBSM). When such a mutation occurs at one of the loci in a profile, it has the effect that the associated allele is not visible in the profile. In the case where a person has two different alleles at a given locus (heterozygous) the effect of a PBSM would be that the profile would appear to be that of an individual with only one allele at that locus (homozygous). The paper investigates the potential for an adventitious match as a result of a PBSM when, for example, a crime profile and person profile that have originated from two different individuals are found to be the same as a result of a PBSM in one of the profiles. It is demonstrated, both by theory and using simulations, that the effect of PBSMs is to slightly decrease the adventitious match probability from what it would had the same DNA system been used.